The Long-Term Impacts of International Migration Evidence from a Lottery - Gibson, John (World Bank E-Library Archive, 2015)
This study examines the long-term impacts of international migration by comparing immigrants who had successful ballot entries in a migration lottery program, and first moved almost a decade ago, with people who had unsuccessful entries into those same ballots. The long-term gain in income is found to be similar in magnitude to the gain in the first year, despite migrants upgrading their education and changing their locations and occupations. This results in large, sustained benefits to the migrants' immediate family, who have substantially higher consumption, durable asset ownership, savings, and dietary diversity. In contrast, the study finds no measureable impact on extended family